PELP1 Suppression Inhibits Colorectal Cancer through c-Src Downregulation. (22nd May 2014) - Ning, Zhifeng; Zhang, Youzhi; Chen, Hanwei; Wu, Jiliang; Song, Tieshan; Wu, Qian; Liu, Fuxing
Abstract : Proline-, glutamic acid-, and leucine-rich protein 1 (PELP1), a coregulator of estrogen receptors alpha and beta, is a potential protooncogene implicated in several human cancers, including sexual hormone-responsive or sexual hormone-nonresponsive cancers. However, the functions of PELP1 in colorectal cancer remain unclear. In this study, western blot and bioinformatics revealed that PELP1 expression was higher in several colorectal cancer cell lines than in immortalized normal colorectal epithelium. PELP1 silencing by short hairpin RNA promoted the senescence and inhibited the proliferation, colony formation, migration, invasion, and xenograft tumor formation of the CRC cell line HT-29. Moreover, PELP1 silencing was accompanied by c-Src downregulation. c-Src upregulation partly alleviated the damage in HT-29 malignant behavior induced by PELP1 RNA interference. In conclusion, PELP1 exhibits an oncogenic function in colorectal cancer through c-Src upregulation.